The Arabidopsis Cop9 signalosome subunit 4 (CSN4) is involved in adventitious root formation - Daniel Ioan Pacurar (Nature Portfolio, 2017)
Abstract The COP9 signalosome (CSN) is an evolutionary conserved multiprotein complex that regulates many aspects of plant development by controlling the activity of CULLIN-RING E3 ubiquitin ligases (CRLs). CRLs ubiquitinate and target for proteasomal degradation a vast number of specific substrate proteins involved in many developmental and physiological processes, including light and hormone signaling and cell division. As a consequence of CSN pleiotropic function, complete loss of CSN activity results in seedling lethality. Therefore, a detailed analysis of CSN physiological functions in adult Arabidopsis plants has been hampered by the early seedling lethality of csn null mutants. Here we report the identification and characterization of a viable allele of the Arabidopsis COP9 signalosome subunit 4 (CSN4). The allele, designated csn4-2035, suppresses the adventitious root (AR) phenotype of the Arabidopsis superroot2-1 mutant, potentially by altering its auxin signaling. Furthermore, we show that although the csn4-2035 mutation affects primary and lateral root (LR) formation in the 2035 suppressor mutant, CSN4 and other subunits of the COP9 complex seem to differentially control AR and LR development.